Fiji before the storm: Elections and the politics of development - V. Lal, Brij (ANU Press, 2012)
A racially-weighted Constitution, promulgated by decree in 1990, divided the country and invited international condemnation, and the economy suffered from the collapse of institutions of good governance. In 1995, an independent Constitution Review Commision appointed by the Fijian parliament, recommended wide-ranging changes to the Constitution. Its report formed the basis of a new Constitution promulgated, after wide-ranging consultation and debate, in 1997. Two years later, Fiji held a general election under it. This collection of essays looks at the politics and dynamics of that momentous event, and the role of key individuals and institutions in producing an outcome that, a year later, plunged Fiji into its first major crisis of the twenty-first century. The essays look at some of the key political and development issues on the eve of the crisis, but the relevance to the current debates about the nature and meaning of politics in Fiji remains. All the contributors are recognised and longstanding specialists in their fields.